Core Tax Administration System and Taxpayer Compliance in the Digital Era - Mariana Salosso; Roberth Kurniawan Ruslak Hammar (Scieclouds Publishing, 2026)
The rapid advancement of digital technologies has encouraged governments worldwide to modernize tax administration systems to improve efficiency, transparency, and taxpayer compliance. In Indonesia, the Directorate General of Taxes has introduced the Core Tax Administration System (CTAS), an integrated digital platform designed to consolidate various tax administration functions within a unified ecosystem. This study aims to examine the effect of CTAS implementation on taxpayer compliance in the digital era. A quantitative explanatory research design was employed, involving 110 registered taxpayers at the Primary Tax Office in Manokwari, West Papua, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The measurement model evaluation demonstrated satisfactory validity and reliability, with all indicators meeting the required thresholds for outer loading, Average Variance Extracted (AVE), Composite Reliability, and Cronbach’s Alpha. The structural model results revealed that CTAS implementation has a positive and statistically significant effect on taxpayer compliance (β = 0.741; T = 12.483; p < 0.001). The coefficient of determination (R² = 0.549) indicates that CTAS explains 54.9% of the variance in taxpayer compliance. Furthermore, the effect size (f² = 1.216) suggests a substantial contribution of CTAS to compliance behavior. These findings indicate that integrated digital tax administration systems can enhance taxpayer compliance by improving accessibility, reliability, service quality, security, and administrative efficiency. The study concludes that CTAS represents an important instrument for supporting tax administration modernization and promoting voluntary compliance. Future policies should complement technological innovation with taxpayer education, digital literacy programs, and service quality improvements to maximize the benefits of digital taxation reforms.